Peroneus brevis split tear – A challenging diagnosis: A pictorial review of magnetic resonance and ultrasound imaging. Part 1. Anatomical basis and clinical insights - Katarzyna Bokwa-Dąbrowska; Rafał Zych; Dan Mocanu; Michael Huuskonen; Dawid Dziedzic; Pawel Szaro (European Journal of Radiology Open)
Diagnosing peroneus brevis split tears is a significant challenge, as many cases are missed both clinically and on imaging. Anatomical variations within the superior peroneal tunnel can contribute to peroneus brevis split tears or instability of the peroneal tendons. However, determining which anatomical variations predispose patients to these injuries remains challenging due to conflicting data in the literature. In this review, we present the current understanding of the role of anatomical variants in the development of peroneus brevis split tears. Many studies emphasize the significance of the retromalleolar groove and retromalleolar tubercle, the impact of a low-lying muscle belly, and the presence of accessory muscles within the superior peroneal tunnel as contributors to peroneal pathology. Hypertrophy of the peroneal tubercle or post-traumatic irregularities in the surface of the retromalleolar groove can accelerate degenerative changes in the peroneal tendons, potentially leading to peroneus brevis split tears. The topographic anatomy of the superior peroneal tunnel is essential for systematically performing ultrasound and interpreting magnetic resonance imaging of the ankle. The first part of this review focuses on the anatomical foundations of imaging diagnostics for peroneus brevis pathology. In the second part, we will examine the radiological spectrum of peroneal tendon injuries, offering a framework to enhance diagnostic confidence in this frequently underdiagnosed pathology.